Using the interest rate tool to control inflation in Vietnam - Dau, Vu Thi (VNU Journal of Science: Legal Studies; Vol 20 No 1E, 2004)
Inflation is considered as a phenomenon associating with the market economy, so in modern economic circumstances, controlling inflation is one of the essential targets of each nation. However, how to control inflation is not easy as inflation results from different causes and occurs in different economic and social circumstances in different nations, which makes use of the different interest rate tools in controlling inflation to gain various goals. This article discusses the use of the interest rate tool in controlling inflation in Vietnam - based on the successful lessons and the limitations of this tool.